2006
DOI: 10.1080/01421590600825292
|View full text |Cite
|
Sign up to set email alerts
|

Use of script concordance test to assess pharmaceutical diabetic care: a pilot study in Thailand

Abstract: The script concordance (SC) test is an assessment tool designed to probe whether knowledge of examinees is efficiently organized for clinical actions. The aim of this study was to develop an SC test, and determine whether it could be used to differentiate novices from expert pharmacists in their ability to carry out clinical actions in the area of diabetes mellitus. The SC test was developed and validated according to guidelines proposed previously. Data analysis was performed using a post-hoc test and ANOVA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…Novices, residents, and experts demonstrated significantly different levels of reasoning, and SCT scores were positively correlated to training level. Because numerous studies have tested this concept (of concurrent validity) at the composite score level and reported similar findings, [15][16][17][18][19] we were not surprised to observe that all six scoring methods differentiated between training levels and that scores correlated with level of development.…”
Section: Scoring Methods Analysissupporting
confidence: 53%
“…Novices, residents, and experts demonstrated significantly different levels of reasoning, and SCT scores were positively correlated to training level. Because numerous studies have tested this concept (of concurrent validity) at the composite score level and reported similar findings, [15][16][17][18][19] we were not surprised to observe that all six scoring methods differentiated between training levels and that scores correlated with level of development.…”
Section: Scoring Methods Analysissupporting
confidence: 53%
“…Script concordance hinges on an inference that examinees with more evolved illness scripts will interpret data and make decisions that increasingly concord with those of experts given the same clinical scenarios. Indeed, SCTs used in various domains of medicine have consistently demonstrated that scores tend to increase with increasing levels of training 4,23,27,28 …”
Section: Building a Validity Argumentmentioning
confidence: 99%
“…Over the last 10 years, research into the theoretical underpinnings and psychometric properties of script concordance has accumulated. The SCT has garnered interest for use in a wide and disparate array of health‐related fields 2–6 . In neurology, a call for a national initiative to promote script concordance assessment in undergraduate and postgraduate training programmes in Canada was recently sounded 7…”
Section: Introductionmentioning
confidence: 99%
“…17 Advantages of using the SCT are that it provides an indication of a student's clinical reasoning ability in real-life situations where there is uncertainty. 13,18,19 The objectives of this study were to develop and assess pharmacy students' clinical reasoning in basic emergency situations using the SCT.…”
Section: Introductionmentioning
confidence: 99%